2014
DOI: 10.1002/chem.201402611
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of van der Waals Complexes between Borylenes and Hydrocarbons

Abstract: The addition of borylenes (RB) to prototypical carbon-carbon multiple bonds (ethyne, ethene) and the insertion into a C-H bond of methane involves weakly bound van der Waals complexes of the reaction partners according to computational chemistry methods. Geometries of all complexes were optimized using spin-component scaled second-order Møller-Plesset perturbation theory (SCS-MP2) in combination with a quadruple-ζ (def2-QZVP) basis set. Energies were further refined using the coupled-cluster (CCSD(T)) method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…The transition state structures that were found to link the coordinated CF 3 H and BR systems (Figure a) to the insertion product (Figure c) are shown in Figure . They are quite similar to structures identified in refs and for borylene insertion into the CH bonds of methane.…”
Section: Results and Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The transition state structures that were found to link the coordinated CF 3 H and BR systems (Figure a) to the insertion product (Figure c) are shown in Figure . They are quite similar to structures identified in refs and for borylene insertion into the CH bonds of methane.…”
Section: Results and Discussionsupporting
confidence: 85%
“…The chemistry of borylenes, including base-stabilized borylenes, has expanded in the past decade to include careful assessments of their potential viability as ligands. ,,, We consider in the next sections the tendencies of borylene species to engage in σ-hole interactions and to form complexes with Lewis acids, specifically monofluoromethane and its Si and Ge analogues.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available experimental evidence from trapping studies suggests that borylenes RB are highly reactive transient species. Computational analysis of the reactions with prototypical carbon multiple bonds has revealed that borylenes behave as electrophilic species because of their vacant p orbitals. , The transition states for cycloaddition resemble those of carbenes, and changes in barrier heights, distances, and angles can similarly be associated with varying borylene philicities. , …”
Section: Introductionmentioning
confidence: 99%